2016
DOI: 10.1002/bjs.10128
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the concordance of histological grade of breast cancer between core needle biopsy and surgical excision specimen

Abstract: Grading on CNB corresponds moderately with grading based on excision specimens, with underestimation in about one in five patients. Incorrect CNB tumour grading has limited clinical implications, as multiple factors influence decision-making for adjuvant systemic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 76 publications
3
19
0
Order By: Relevance
“…When assessing tumor grade on CNB and FUE, discordance rates did not differ more than one grade . Previous studies have reported underestimation of tumor grade on CNB to be up to 20% . In our study, the CNB was found to predict tumor grade and mitotic rate of IMCs in 82% of FUEs.…”
Section: Discussionsupporting
confidence: 58%
“…When assessing tumor grade on CNB and FUE, discordance rates did not differ more than one grade . Previous studies have reported underestimation of tumor grade on CNB to be up to 20% . In our study, the CNB was found to predict tumor grade and mitotic rate of IMCs in 82% of FUEs.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies showing that intertumoral metabolic heterogeneity is more pronounced than intratumoral metabolic heterogeneity (32) and that core biopsy samples can be used to reliably assess intertumoral differences (33)(34)(35)(36)(37) provided us with a rationale for comparing global imaging-based metrics (mean LAC/PYR and mean summed SNR LAC ) with the results from IHC and RNA sequencing of single tumor biopsies. The strong correlation between the LAC/PYR with tumor volume, which is known to correlate with hypoxia (38), led us to investigate the contribution of hypoxia to the measured lactate signal.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore do not expect that this influences the model validity. However, discrepancy of tumor grade between core needle biopsies and excision specimen was reported to be near 30% in a recent meta-analysis 36 . It may be that this discrepancy has influence on the performance of the model.…”
Section: Accepted Manuscriptmentioning
confidence: 98%